Pengaruh Transfer Pemerintah Terhadap Kinerja Fiskal Pemerintah Daerah Kabupaten Manokwari Dalam Pelaksanaan Desentralisasi Fiskal - Siti Aisah Bauw; Lillyani M. Orisu; Melkion D.T. Worabay (JFRES Journal of Fiscal and Regional Economy Studies, 2018)
Government transfers are one of the central government's interventions in autonomous regions that aim to help regions with low fiscal capacity. With the development of transfers in Manokwari Regency which is always increasing, describing government spending in financing development still depends on the central government or balance funds. The purpose of this study was to etermine the effect of government transfers on the fiscal erformance of Manokwari Regency in the implementation of decentralization. This study is aimed at analyzing he influence of government transfers on the fiscal performance of the Manokwari District government in the implementation of decentralization. With five years of observation. Model estimation is analyzed using simple linear regression (simple linear regression) by partially testing the hypothesis. The results showed that the variable government transfer index had a positive coefficient (+) on the fiscal performance of the regional government, with a R2 value of 86% indicating a ignificant influence on the fiscal performance of the local government.